Small Scale Industry in Sivakasi and Sattur - Planning Commission (Planning Commission, 1957)
In the Second Five Year Plan small scale industries are allotted a distinct role and along with the village and cottage industries, they are to be an integral and continuing element both in the economic structure and in the scheme of national planning. The primary object of developing this decentralised sector of industries is to extend work opportunities, raise incomes and standard of living and to bring about a more balanced and integrated economy. Several problems of the small scale industries in different parts of the country are common but there are also regional variations and each industry or group of industries may also have its own peculiar structure and problems. Factual and analytical studies on a local or regional basis can bring out these peculiarities and serve as the basis for formulating suitable lines of developmental effort. 2. I have selected small scale industries in Sivakasi and Sattur for such a study. With the help of a grant from the Research Programmes Committee of the Planning Commission, I carried out a survey in 1954- 55 of these industries. The general pattern of investigational organisation and technique was recommended to me by the Research Programmes Committee, but the actual techniques of study, analysis and interpretation followed by me in each case are largely of my own choice.
By E. K. Warriar Professor of Economics, Shri Venkateswara University, Tirupati